Proof-of-concept delivery of intensity modulated arc therapy on the Elekta Unity 1.5 T MR-linac. (1st February 2021) - Kontaxis, C; Woodhead, P L; Bol, G H; Lagendijk, J J W; Raaymakers, B W
Abstract: In this work we present the first delivery of intensity modulated arc therapy on the Elekta Unity 1.5 T MR-linac. The machine's current intensity modulated radiation therapy based control system was modified suitably to enable dynamic delivery of radiation, for the purpose of exploring MRI-guided radiation therapy adaptation modes in a research setting. The proof-of-concept feasibility was demonstrated by planning and delivering two types of plans, each investigating the performance of different parts of a dynamic treatment. A series of fixed-speed arc plans was used to show the high-speed capabilities of the gantry during radiation, while several fully modulated prostate plans—optimised following the volumetric modulated arc therapy approach—were delivered in order to establish the performance of its multi-leaf collimator and diaphragms. These plans were delivered to Delta 4 Phantom+ MR and film phantoms passing the clinical quality assurance criteria used in our clinic. In addition, we also performed some initial MR imaging experiments during dynamic therapy, demonstrating that the impact of radiation and moving gantry/collimator components on the image quality is negligible. These results show that arc therapy is feasible on the Elekta Unity system. The machine's high performance components enable dynamic delivery during fast gantry rotation and can be controlled in a stable fashion to deliver fully modulated plans.